Pilot Testing of a Nurse-Led Basic Symptom Self-management Support for Patients Receiving First-Line Systemic Outpatient Anticancer Treatment: A Cluster-Randomized Study (Symptom Navi Pilot Study). Issue 6 (November 2021) - Bana, Marika; Ribi, Karin; Peters, Solange; Kropf-Staub, Susanne; Näf, Ernst; Zürcher-Florin, Sabin; Stoffel, Barbara; Blaeuer, Cornelia; Borner, Markus; Malin, Diana; Biber, Rebecca; Betticher, Daniel; et al.
Abstract : Background: The Symptom Navi Program (SNP) is a nurse-led intervention supporting basic symptom self-management for patients with any cancer diagnosis. The SNP has been accepted by patients and healthcare professionals alike. Objective: The aims of this study were to pilot the SNP and evaluate patient-reported symptom outcomes, nursing support for symptom management, and patient safety. Methods: Using a cluster-randomized design, we randomized centers to the intervention (SNP) or control group (usual care). Adult patients starting first-line systemic cancer treatment were included. The primary outcome was the change in symptom interference with daily functions from treatment onset to 16 weeks. Secondary outcomes included changes in symptom severity, symptom burden, self-efficacy, and perceived symptom management support and patient safety. We used linear and logistic mixed-effects models to pilot-test differences in mean changes between groups. The trial was registered with ClinicalTrials.gov (NCT03649984). Results: Changes in symptom interference with daily functions did not differ (mean difference at 16 weeks: −0.50; 95% confidence interval, −1.38 to 0.38; P = 0.25) between SNP (3 centers, 49 patients) and control (5 centers, 85 patients) as for all other outcomes. No adverse events were reported. Conclusions: Our preliminary findings did not indicate an effect of the SNP on patient-reported symptom outcomes, self-efficacy, or symptom management support. Inadequate power and SNP components (eg, insufficient training, low number of follow-up consultations) may be attributed to the lack of an observed effect. Implications for Practice: The SNP training content and intervention procedures merit reconsideration. Abstract : The Symptom Navi Program was appreciated by patients and accepted by healthcare professionals, yet pilot testing did not show an effect on symptom interference with daily function.